Reactive oxygen species (ROS) as defenses against a broad range of plant fungal infections and case study on ROS employed by crops against Verticillium dahliae wilts. Issue 1 (1st January 2018) - Ali, Muhammad; Cheng, Zhihui; Ahmad, Husain; Hayat, Sikandar
ABSTRACT: Reactive oxygen species (ROS) are natural by products of cellular metabolism that were initially considered only deleterious towards the cellular macromolecules. Research advances have broadened the scope and now numerous studies are available rendering ROS molecules essential for plants to combat several biotic and abiotic stresses after being involved in essential defense mechanisms such as hypersensitivity reactions (HR) that lead to programmed cell death (PCD), cell wall reinforcement by cross-linking of cellular glycoproteins with other entities and salicylic acid mediated signal transduction pathways. During fungal attack, the fungal components like chitin and other elicitors activates the plant immune responses that employ ROS with other molecules like nitric oxide (NO), calcium ions to fight back the pathogen attack and restrict its spread to further plant parts. Here, several defense mechanisms mediated by ROS are discussed. Verticillium dahliae is one of the dreadful fungal pathogen to plants that cause wilts in many important plant species causing huge economic burden in food sector. The major constraint in its scenario being the deficit of field management systems based on chemicals or agronomics. It is evident by studying their interactions with the variety of hosts that in most cases, ROS mediated defenses play a key central role via cross-talk with other mechanisms making them a potential target for transgenics as well as resistant genotype selection.